The nomogram predicting the early failure rate of the Pavlik harness for developmental dysplasia of the hip in infants under 6 months of age - Gou, Pan; Gao, Kai; Wang, Xiaoting; Liu, Xing (Frontiers in Pediatrics, 2022)
Background: The aim of our study was to develop a nomogram predicting the early failure rate of Pavlik harness in infants under 6 months of age with developmental dysplasia of the hip (DDH). Methods: We retrospectively analyzed the clinical data of 227 patients (372 hips) with DDH who were treated with Pavlik harness at our institution from August 2020 to June 2021. Fifty-eight patients (102 hips) failed the Pavlik harness treatment and 169 patients (270 hips) were successfully treated. Then the independent risk factors for treatment failure were determined via univariate and multivariate logistic regression and used to generate the nomogram predicting the failure rate of the Pavlik harness. Results: It was found that age at initial treatment (OR 1.031, 95% CI 1.022-1.040, P＜0.001 ), angle α (OR 0.723, 95% CI 0.671-0.779, P＜0.001) and concomitant deformity (OR 0.129, 95% CI 0.036-0.459, p = 0.002) were independent risk factors for treatment failure. The nomogram showed good discrimination ( the area under the curve [AUC]: 0.862), good calibration and a net benefit in the range of probabilities between 5 and 90% according to the decision curve analysis. Conclusions: This study had successfully established the nomogram prediction model based upon three independent risk factors. Due to high level of predicting accuracy, this nomogram could be useful resources for pediatric orthopaedic surgeons to identify patients at major risk of Pavlik harness failure who might need more reliable treatments.